2006
DOI: 10.1002/hep.21088
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hepatitis C virus E2 epitope defined by the broadly neutralizing monoclonal antibody AP33

Abstract: The mouse monoclonal antibody (MAb) AP33, recognizing a 12 amino acid linear epitope in the hepatitis C virus (HCV) E2 glycoprotein, potently neutralizes retroviral pseudoparticles (HCVpp) carrying genetically diverse HCV envelope glycoproteins. Consequently, this antibody and its epitope are highly relevant to vaccine design and immunotherapeutic development. The rational design of immunogens capable of inducing antibodies that target the AP33 epitope will benefit from a better understanding of this region. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
176
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(193 citation statements)
references
References 47 publications
17
176
0
Order By: Relevance
“…Similarly, W420A mutation abolished both MAb AP33 (itself a broadly neutralizing antibody [39]) and CD81 binding, indicating overlap between the CD81 binding site and the AP33 epitope. Finally, mutations at L413, N415, and G418 also reduced the binding of MAb AP33, and we have recently shown that these, together with W420, are probable contact residues (47).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Similarly, W420A mutation abolished both MAb AP33 (itself a broadly neutralizing antibody [39]) and CD81 binding, indicating overlap between the CD81 binding site and the AP33 epitope. Finally, mutations at L413, N415, and G418 also reduced the binding of MAb AP33, and we have recently shown that these, together with W420, are probable contact residues (47).…”
Section: Discussionmentioning
confidence: 71%
“…The majority of the substitutions were tolerated by MAb AP33, although binding to mutants L413A, N415A, G418A, and W420A was reduced by at least 50% compared to the wild-type protein. We have recently shown that these residues form part of the AP33 epitope (47). Recognition of the mutant proteins by three conformation-depen-FIG.…”
Section: Resultsmentioning
confidence: 99%
“…These mutations were not found in virus passaged in parallel without AP33 neutralization. Although N415 is within a domain identified previously as comprising the AP33 epitope 413-420 (22,23), E655 is distant in the linear E2 sequence and has not been implicated previously in recognition of HCV by AP33. To validate the role of these mutations in conferring neutralization escape, they were engineered both singly and together into pHJ3-5 plasmid DNA, and the cognate viruses rescued after RNA transfection of naive cells.…”
Section: Resultsmentioning
confidence: 89%
“…Importantly, immunization of mice and rats with recombinant E2 also elicits mAbs that recognize this E2 segment (20)(21)(22). One such mAb, AP33, is of particular interest because it demonstrates broad and potent, cross-genotypic neutralizing activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation